2013
DOI: 10.1175/mwr-d-12-00013.1
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivities of a Squall Line over Central Europe in a Convective-Scale Ensemble

Abstract: Convective-scale ensemble simulations with perturbed initial and lateral boundary conditions are performed to investigate the mechanisms and sensitivities of a central European convection event from the Convective and Orographically Induced Precipitation Study (COPS). In this event, a ''primary'' squall line developed ahead of a decaying mesoscale convective system (MCS) upstream of the Vosges Mountains (France), weakened over the Rhine valley, then regenerated as a ''secondary'' squall line over the Black For… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
34
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 53 publications
3
34
0
Order By: Relevance
“…Sensitivity fields were investigated with regard to the driving synoptic flow aloft as well as the mesoscale features closer to the surface that might be important to the dynamics of the convective event. Like with Hanley et al (2013), the variability in the convection forecast was found to be related to positional shifts in synoptic-scale features both at upper and lower levels of the troposphere. A faster upper-level low would be consistent with faster progression of low-level features.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Sensitivity fields were investigated with regard to the driving synoptic flow aloft as well as the mesoscale features closer to the surface that might be important to the dynamics of the convective event. Like with Hanley et al (2013), the variability in the convection forecast was found to be related to positional shifts in synoptic-scale features both at upper and lower levels of the troposphere. A faster upper-level low would be consistent with faster progression of low-level features.…”
Section: Discussionmentioning
confidence: 68%
“…Each of these studies has shown the value ESA provides in revealing the atmospheric flow features important to the predictability of the specific phenomena they address. One study that has examined convective-scale ensemble forecast sensitivity is Hanley et al (2013), which used a precipitation-based response function within a 4-km grid to examine the role of the PV field aloft 12 h prior. It was found that ESA revealed an area at the edge of a PV anomaly aloft, as well as more interior PV magnitudes, which signaled the importance of the precise nature of the upper-level PV field to the predictability of squall-line convection later in time.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the potential benefits, little research has been done with convection‐permitting ensembles to understand and predict the occurrence of the squalls in tropical regions, compared to the midlatitude severe convective systems (Hanley et al ., ; Bednarczyk and Ancell, ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Hanley et al (2013) conducted convective-scale ensemble simulations to examine the mechanisms of a convective event in central Europe. They demonstrated that ensemble members that better represented upper-level potential vorticity were in closer agreement with observations in terms of the development of squall lines in the convective event.…”
Section: Introductionmentioning
confidence: 99%